Avaliação da cor e comportamento espectral de algumas classes de solos do Rio Grande do Sul - Botelho, Márcio Ramos (2005)
The soil color is a characteristic easily determined, through the visual comparison with the Munsell Charts and is related to the presence of iron oxide and organic matter in the soil. The obtention of the color trough instruments as colorimeters and spectroradiometers tend to increase precision since are done under controlled conditions. The objective of study 1 of this work was to compare the color of different soils of the Rio Grande do Sul, determined through the Munsell Charts with the measures made by colorimetry. The coefficients of correlation obtained had indicated that coherence between the color measures carried through for different observers (Munsell Charts) and the colorimeter. The precision of the observers in the determination of the color for the same soil sample was evaluated, with lesser variability for the component shade and greater difficulty in the evaluation of chromes. The colorimeter showed to be efficient when used to quantify the color, eliminating possible psychophysical errors attributed to the visual method. Radiometers or spectroradiometers record the energy reflected from the soil in the wavelengths of visible and the infrared region of the electromagnetic specter, in a numerical or graphical data sets called spectral curves. The existing relations between the spectral behavior and the specific soil characteristics, as texture, content organic matter and iron oxides, allow distinguishing soils classes and the quantification of some characteristics through the spectral curves. The objective of study 2 was to relate the physical, chemical, and mineralogical characteristics with the spectral behavior of different soils classes of the RS in the 400 to 2500 nm interval of the optic specter to seek an agreement of the effect of the spectral interaction with the different soil components. The results obtained in study 2 had shown that it is possible to identify and to correlate the soil haracteristics as the content organic matter, iron oxides, color and granulometry through the soil spectroradiometry.